Multiple insect pollination contributes to differential phenotypic selection on floral traits in Stellera chamaejasme - Shu-Fan Sun; Yan-Bao Li; Jing Leng; Ding-Hai Zhang; Wen-Liu Zhang; Bo Zhang (BMC Plant Biology)
Abstract Background Flower morphology is believed to be primarily shaped by the most important pollinators when more than one pollinating species visits the flowers. However, floral adaptation to the selection mediated by multiple pollinators has received little attention. The plant Stellera chamaejasme has evolved a pollination syndrome matching both lepidopteran and thrips. In this study, to test the relative importance of different pollinators to the plant’s reproductive success and clarify how phenotypic selection on floral traits relates to different functional groups of pollinators, we determined the relative contributions of different pollinating insects to plant reproductive fitness through pollinator manipulation experiments and investigated the associated phenotypic selection on floral traits. Results Lepidopterans and thrips had comparable contributions to the reproductive fitness of S. chamaejasme. Among lepidopterans, the fitness contribution was distinctly higher for moths than for butterflies. Corolla opening size (i.e., corolla entrance) was subject to positive directional selection mediated mainly by lepidopterans, with thrips exerting opposing directional selection for this trait. The significant correlational selection between tube length and corolla opening size suggested that thrips and lepidopteran pollinators favored either the broad-entranced short flowers or the narrow-entranced long flowers. Conclusions Most likely, a functionally integrated adaptation to accommodate a variety of pollinators led to the floral design of S. chamaejasme, which in turn contributed to the diversity of flowers. Clinical trial number Not applicable.